Unlocking Pinus ponderosa (Douglas ex C. Lawson) potential: a comprehensive review of results from native and introduced areas - Tomczak, Karol; Vacek, Zdeněk; Cukor, Jan; Vacek, Stanislav; Bažant, Václav; Zeidler, Aleš; Trojan, Václav; Gallo, Josef; Černý, Jakub (Frontiers in Forests and Global Change, 2025)
Ponderosa pine (Pinus ponderosa) is one of the most valuable American pines growing naturally in the western and Pacific states of Arizona and California. Based on previously published research, its ecological valence makes this species suitable for introduction worldwide, including Europe. In Central Europe, climate change—the primary cause of significant dieback of native tree species, such as Norway spruce and Scots pine—has increased the need to explore new methods to ensure forest stand sustainability. Introducing previously overlooked tree species, such as ponderosa pine could help address this challenge. We reviewed 229 research sources to analyze P. ponderosa’s potential for utilization in new areas. The existing research from its native distribution range indicates ecological plasticity and strong resistance to drought and climatic extremes. Production parameters were evaluated in young European forest stands with a stand volume of 430 m3⋅ha–1 at the age of 45, pointing toward a promising use in the forestry sector. In European forestry, ponderosa pine’s importance could grow due to its adaptability to warm and dry climates and tolerance of diverse soil conditions. Moreover, the extraordinary quality and texture of the wood, as well as ponderosa’s biodiversity and ornamental functions, make the species destined to become part of future landscapes and forest ecosystems of Central Europe under changed climatic conditions. However, we also see challenges and scientific gaps associated with the management of ponderosa pine and its introduction to mixtures with native tree species without prior verification and silviculture recommendations.